"Are the working principles of fisheries management at work in Indonesia?". (June 2022) - Jaya, Indra; Satria, Fayakun; Wudianto,; Nugroho, Duto; Sadiyah, Lilis; Buchary, Eny A.; White, Alan T.; Franklin, Erik C.; Courtney, Catherine A.; Green, Gina; Green, Stuart J.
Abstract: Indonesia, the world's largest archipelagic nation and second-largest fish producer in the world, has fisheries distinguished by a high diversity of species and with a large variety of gear and methods used to fish over expansive geographic areas. Fisheries management in Indonesia is equally complex with multiple levels of governance, decentralization, and traditional fishing tenure rights. The Government of Indonesia is taking strides to improve fisheries management in a changing and complex environment to support sustainable economic development, livelihoods, and food security of its people. This paper takes stock of recent developments in fisheries science and management in the country and identifies additional opportunities for improvement. An analytic framework for evaluating progress and opportunities for fisheries management has been adapted from a set of eight working principles for effective fisheries management. Analysis of each principle revealed that although current Indonesian fishery management includes landing data collections, onboard observer programs, logbooks, e-logbooks, catch per unit effort (CPUE) standardization, regional fisheries management units, genetic assessments, vessel tracking, and similar tools to improve fisheries management, significant work remains. Although the use of data is pivotal in the development of fisheries solutions, data inputs are still not adequate to perform fully reliable assessments. Indonesia's pool of experts remains insufficient to meet the extensive stock assessment needs across the country and thus continuous training and mentoring of assessors in techniques relevant for different stock types and data levels is crucial to ensure skills enhancement. Indonesia's interdisciplinary stock assessment review body, Komnas KAJISKAN, plays a critical role by providing scientific guidance that balances short-term economic needs from the perspectives of fishers and policymakers with the ecological constraints required for long-term fishery sustainability. Although small-scale fisheries dominate Indonesia's fisheries management system, the process of decentralizing data collection and management functions to province, district, and village levels is alone not sufficient to encourage more local ownership and compliance. Tools such as customary rules of conduct, marine protected areas, and other local area management regimes can also help to successfully manage small-scale fisheries and marine resources. Provincial licensing and boat classifications remain issues that require continued attention, simplification, and clarification. Finally, an enhanced national policy framework that empowers and engages local governments, universities, NGOs, fishers and community groups who are adequately trained, staffed, and funded would significantly strengthen fisheries science through improved data collection, processing, and interpretation to benefit management. In conclusion, the threat of overfishing in Indonesia's fisheries is visible in the data, and trends suggest a similar pathway involving unsustainable production goals and escalating overfishing as followed by neighboring countries that experienced fisheries collapse. Time is of the essence in recognizing this trajectory and adjusting policies to maintain and sustain the country's natural fisheries wealth for the present and future generations.